Studies of Nanoconstrictions, Nanowires and Feb3(BOb4 (BThin Filmss Electrical Conduction and Magnetic Properties. Fabrication by Focused Electron/Ion Beam - Fernandez-Pacheco, Amalio; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This work constitutes a detailed study of electrical and magnetic properties in nanometric materials with a range of scales: atomic-sized nanoconstrictions, micro- and nanowires and thin films. Firstly, a novel method of fabricating atomic-sized constrictions in metals is presented; it relies on measuring the conduction of the device while a focused-ion-beam etching process is in progress. Secondly, it describes wires created by a very promising nanolithography technique: Focused electron/ion-beam-induced deposition. Three different gas precursors were used: (CHb3(B)b3(BPt(CpCHb3(B), W(CO)b6 (Band Cob2(B(CO)b8(B. The thesis reports the results obtained for various physical phenomena: the metal-insulator transition, superconducting and magnetic properties, respectively. Finally, the detailed magnetotransport properties in epitaxial Feb3(BOb4 (Bthin films grown on MgO (001) are presented. Overall, the new approaches developed in this thesis have great potential for supporting novel technologies.s
Introduction -- Experimental Techniques -- Magnetotransport Properties of Epitaxial Fe3O4 thin Films -- Conduction in in Atomic-Sized Magnetic Metallic Constructions created by FIB -- Pt-C Nanowires created by FIBID and FEBID -- Superconductor W-Based Nanowires created by FIBID -- Magnetic Cobalt Nanowires created by FEBID -- Conclusions and Outlook -- CV.
Keywords: Nanotechnology; Materials Science; Nanotechnology; Nanoscale Science and Technology; Surface and Interface Science, Thin Films